Robotized hardfacing on high-strength steels: determination of impact properties with different heat inputs - Ákos Meilinger; Gábor Terdik (Journal of Advanced Joining Processes)
The use of high-strength steels as a substrate for hardfacing is becoming increasingly common in the industry (e.g., for demolition shears). In the case of joint welding, the weldability of these steels is limited because welding heat has significant affect to the base material. Both softening and hardening can occur in the different sub-zones of heat-affected zone, leading to changes in impact properties. For demolition shears, impact stresses are the most critical loads. Heat input can alter the microstructure of the heat-affected zone, potentially reducing the load-bearing capacity due to the penetration depth of the hardface layer or the buffer layer. Robotization of hardfacing creates equal layers with high precision, which helps the precise comparison. In this study, S690QL and S960QL substrates were investigated under different heat inputs, and the impact properties of these specimens were tested. Instrumented impact test results were analyzed and supplemented with surface fractography. The impact resistance of the S690QL substrate decreases with higher heat input and penetration depth. In contrast, S960QL exhibits different behavior: the use of lowest heat input causes a 226 % increase in impact energy compared with the base material. The underlying reasons for this were identified through force-time curve analysis, where the positive effect of the heat-affected zone is determined. Additionally, the maximum impact forces display different behavior for the two materials: S960QL shows higher impact force except in case of highest heat input, where the S690QL shows better force. These findings are valuable for selecting the appropriate substrate and hardfacing technology for this application and its specific loading conditions.